Energy Performance of a High-Rise Residential Building Using Fibre-Reinforced Structural Lightweight Aggregate Concrete - Zakaria Che Muda; Payam Shafigh; Norhayati Binti Mahyuddin; Samad M.E. Sepasgozar; Salmia Beddu; As’ad Zakaria (Applied Sciences, 2020)
The increasing need for eco-friendly green building and creative passive design technology in response to climatic change and global warming issues will continue. However, the need to preserve and sustain the natural environment is also crucial. A building envelope plays a pivotal role in areas where the greatest heat and energy loss often occur. Investment for the passive design aspect of building envelopes is essential to address CO 2 emission. This research aims to explore the suitability of using integral-monolithic structural insulation fibre-reinforced lightweight aggregate concrete (LWAC) without additional insulation as a building envelope material in a high-rise residential building in the different climatic zones of the world. Polypropylene and steel fibres in different dosages were used in a structural grade expanded clay lightweight aggregate concrete. Physical and thermal properties of fibre reinforced structural LWAC, normal weight concrete (NWC) and bricks were measured in the lab. The Autodesk@Revit-GBS simulation program was implemented to simulate the energy consumption of a 29-storey residential building with shear wall structural system using the proposed fibre-reinforced LWAC materials. Results showed that energy savings between 3.2% and 14.8% were incurred in buildings using the fibre-reinforced LWAC across various climatic regions as compared with traditional NWC and sand-cement brick and clay brick walls. In conclusion, fibre-reinforced LWAC in hot-humid tropical and temperate Mediterranean climates meet the certified Green Building Index (GBI) requirements of less than 150 kW∙h∙m−2. However, in extreme climatic conditions of sub-arctic and hot semi-arid desert climates, a thicker wall or additional insulation is required to meet the certified green building requirements. Hence, the energy-saving measure is influenced largely by the use of fibre-reinforced LWAC as a building envelope material rather than because of building orientation.